1995
DOI: 10.1177/000456329503200215
|View full text |Cite
|
Sign up to set email alerts
|

Lower Values for Immunoglobulin M in Cerebrospinal Fluid When Sampled with an Atraumatic Sprotte Needle Compared with Conventional Lumbar Puncture

Abstract: SUMMARY. Immunoglobulin M (lgM) has a very low concentration in cerebrospinal fluid (CSF) compared with serum, and therefore determinations of IgM in CSF are highly sensitive to pre-analytical errors caused by contamination with serum or interstitial fluid. Capillary attraction causes a thin layer of liquid containing serum proteins to be formed inside a conventional (Quincke) needle during penetration of tissue. To investigate this source of pre-analytical error, 35 patients had lumbar punctures using a 22 G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, atraumatic needles are recommended by most of the 37 articles as the best needle to perform LPs. Indeed, when comparing different needle designs, atraumatic needles resulted in a lower prevalence of post‐LP complaints, including PLPH, low back pain or nausea/vomiting (Table 4) [5,36,48,49,53,54,57,58,60,61,63–67,71,75,79–91]. A lower frequency of complications results in reduced health care costs due to less medication or medical assistance, such as blood patches [48,49,53,54,57,61,64,66,75,79–84,86–91,93,96].…”
Section: Resultsmentioning
confidence: 99%
“…However, atraumatic needles are recommended by most of the 37 articles as the best needle to perform LPs. Indeed, when comparing different needle designs, atraumatic needles resulted in a lower prevalence of post‐LP complaints, including PLPH, low back pain or nausea/vomiting (Table 4) [5,36,48,49,53,54,57,58,60,61,63–67,71,75,79–91]. A lower frequency of complications results in reduced health care costs due to less medication or medical assistance, such as blood patches [48,49,53,54,57,61,64,66,75,79–84,86–91,93,96].…”
Section: Resultsmentioning
confidence: 99%
“…However, current protocols all recommend an atraumatic (penpoint) needle, although with different sized gauges (22, 24 or 25 G; Table 1). A study found that conventional needles (compared with atraumatic ones) led to minor serum protein contamination of CSF [104], though this may not affect AD CSF biomarker concentrations (see section 4.2.6).…”
Section: Type Of Puncture Needlementioning
confidence: 99%